Through the storm, through the night : a history of African American Christianity - Harvey, Paul, 1961- (Lanham, Md. : Rowman & Littlefield Publishers, 2011)
Paul Harvey illustrates how black Christian traditions provided theological, institutional, and personal strategies for cultural survival during bondage and into an era of partial freedom. At the same time, he covers the ongoing tug-of-war between themes of "respectability" versus practices derived from an African heritage; the adoption of Christianity by the majority; and the critique of the adoption of the "white man's religion" from the eighteenth century to the present. The book also covers internal cultural, gendered, and class divisions in churches that attracted congregants of widely disparate educational levels, incomes, and worship styles. --from publisher description.
Themes in African American religious history -- Middle passage for the gods: African and African American religions from the Middle Passage to the Great Awakening -- The birth of Afro-Christianity in the slave quarters and the urban North, 1740-1831 -- Through the night: African American religion in the antebellum era -- Day of jubilee: black churches from emancipation to the era of Jim Crow -- Jesus on the main line: black Christianity from the Great Migration through World War II -- Freedom's main line: black Christianity, civil rights, and religious pluralism -- Righteous anger and visionary dreams: contemporary black politics, religion, and culture.
Includes bibliographical references and index.
Keywords: African Americans -- Religion; United States -- Church history; African Americans -- Religion; United States; Church history